Analisis Semantik dalam Lirik Lagu Takkan Terganti Karya Yovie Widianto - Shofiyatul Indah Setya (Signifiѐ, 2024)
Abstract This study aims for: (1) describe the lexical meaning in the lyrics of the song Irreplaceable by Yovie Widianto (2) describe the grammatical meaning in the lyrics of the song Irreplaceable by Yovie Widianto (3) describe the referential meaning in the lyrics of the song Irreplaceable by Yovie Widianto and (4) describes and explains non-referential meanings in the lyrics of the song Won't Be Replaced by Yovie Widianto. In this study the authors used the method of interpreting and parsing data. The collection of material for this research analysis uses the technique of reading literature, observing, and recording which results in four types of meaning, namely, lexical meaning, grammatical meaning, referential meaning, and nonreferential meaning. Semantic analysis is proven to be able to interpret the words used in the lyrics of the song Irreplaceable by Yovie Widianto, starting from the most basic thing, namely research on vocabulary to concluding the meaning of the song lyrics in each line. The lyrics of the song Irreplaceable by Yovie Widianto are about only one love forever. And can't be replaced by anything even if it's a hindrance. Keywords: Semantic Analysis, song lyrics, irreplaceable.